Rare case of accessory cystic artery treated with laparoscopic cholecystectomy - Venu, Vinayak; Rohil, Basant; Nichat, Pramod D.; Mahankudo, Suresh; Majhi, Ashis; Malik, Salman; Peddi, Tanuja (International Surgery Journal, 2024)
Anomalies of the cystic artery are of significant clinical importance during laparoscopic cholecystectomy, with accessory cystic arteries posing a challenge for surgeons due to increased risk of vascular injury and hemorrhage. This case report describes a 45-year-old female patient who underwent laparoscopic cholecystectomy for symptomatic cholelithiasis, during which an accessory cystic artery was identified. Careful dissection and precise intraoperative management allowed for the successful identification and ligation of both the main and accessory cystic arteries, preventing intraoperative complications. The patient had an uneventful recovery and was discharged on postoperative day two. This case emphasizes the importance of preoperative awareness of vascular variations and highlights the need for meticulous surgical technique to avoid potential complications in patients with accessory cystic arteries.